An assessment of genetic diversity and inbreeding in the Noisy Scrub-bird (Atrichornis clamosus) using microsatellite and Major Histocompatibility Complex loci - Cowen, Saul Jesse (Curtin University, 2014)
The noisy scrub-bird is an endangered songbird restricted to the south coast of Western Australia and has a history of population bottlenecks. This study evaluated the impact that genetic bottlenecks had on genetic diversity of this species using neutral (microsatellite) and adaptive (Major Histocompatibility Complex) genes and how this diversity may influence extinction risk. The results have been used to provide recommendations for future conservation management strategies for this species.